AI-Driven Sharia Governance in Islamic Digital Payment Systems: Developing a Contemporary Islamic Law Framework for Ethical and Regulatory Compliance - Muhammad Azam; Rawdah Abdul Karim Mohammad Pharaon; Elsoghair Mahdy; Manal Abdellatif Issa Albabili; Burhan Alsyouf; Bagdat Bagayev (PT. Islamic Research Publiser, 2026)
The rapid advancement of artificial intelligence (AI) and digital financial technologies has transformed the operational landscape of Islamic financial institutions, creating both new opportunities and significant challenges for Sharia governance. As Islamic digital payment systems increasingly rely on AI-driven tools for transaction monitoring, fraud detection, risk assessment, and compliance verification, important questions arise regarding their compatibility with the principles and objectives of Islamic law. This study examines the role of AI in strengthening Sharia governance within Islamic digital payment ecosystems and evaluates its effectiveness in identifying prohibited elements, including riba, gharar, and other forms of financial misconduct. Using a doctrinal legal research methodology supported by comparative analysis and qualitative content analysis, the study examines primary and secondary sources of Islamic law, including the Qur'an, Sunnah, classical fiqh literature, contemporary Sharia governance standards, and regulatory frameworks from selected Islamic finance jurisdictions. The findings suggest that AI can substantially enhance Sharia compliance through real-time monitoring, predictive analytics, and automated auditing mechanisms. However, concerns related to algorithmic transparency, explainability, accountability, and the inherent limitations of AI in performing ijtihad and issuing fatwa-based judgments prevent it from replacing human scholarly authority in Sharia decision-making. The study argues that AI should function as a decision-support tool rather than an autonomous Sharia decision-maker. To address the governance challenges associated with AI implementation, the article proposes a contemporary Islamic law framework built upon five interconnected pillars: Human-Centered Sharia Supervision, Explainable Artificial Intelligence (XAI), Maqasid al-Shariah Compliance, Continuous Sharia Auditing, and Regulatory Accountability. This framework aims to harmonize technological innovation with the ethical, legal, and jurisprudential foundations of Islamic law while ensuring responsible and trustworthy AI deployment in Islamic finance. The study contributes to the growing literature on Islamic FinTech and AI governance by offering a normative framework for regulating AI applications in Islamic digital payment systems.